2016
DOI: 10.1177/1054773815623252
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Motivational Interviewing in Decreasing Hospital Readmission in Adults With Heart Failure and Multimorbidity

Abstract: Hospitalizations are common in heart failure (HF). Multimorbidity, defined as ≥2 comorbid conditions, drives many readmissions. The purpose of this pilot study was to test the effectiveness of motivational interviewing (MI) in decreasing these hospital readmissions. We enrolled 100 hospitalized HF patients into a randomized controlled trial, randomizing in a 2:1 ratio: intervention (n = 70) and control (n = 30). The intervention group received MI tailored to reports of self-care during one home visit and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
(59 reference statements)
1
30
1
1
Order By: Relevance
“…La educación y el autocuidado en pacientes con FC son elementos positivos de las intervenciones para disminuir el riesgo de morbimortalidad (12)(13)(14)(15)(16). Es primordial que se implementen programas específicos para pacientes con FC, ya que existe suficiente evidencia de programas exitosos y costo-efectivos (11).…”
Section: Introductionunclassified
“…La educación y el autocuidado en pacientes con FC son elementos positivos de las intervenciones para disminuir el riesgo de morbimortalidad (12)(13)(14)(15)(16). Es primordial que se implementen programas específicos para pacientes con FC, ya que existe suficiente evidencia de programas exitosos y costo-efectivos (11).…”
Section: Introductionunclassified
“…A recently published study showed that patients with multiple sclerosis improved adherence to an exercise program with the use of MI . A randomized controlled study showed a significant decrease in re‐admission of heart failure patients when MI was conducted by nurses with patients . Another study in heart failure patients specifically trained nurses to provide the MI sessions .…”
Section: Introductionmentioning
confidence: 99%
“…12 A randomized controlled study showed a significant decrease in re-admission of heart failure patients when MI was conducted by nurses with patients. 16 Another study in heart failure patients specifically trained nurses to provide the MI sessions. 5 These studies support that clinicians, including nurses, can be trained to provide MI in multiple settings and little training is needed to conduct MI interventions.…”
Section: Introductionmentioning
confidence: 99%
“…MI was developed in psychology and only recently has the approach been used in chronically ill patient populations. Studies among adults with HF have examined the effect of MI on exercise [6], hospital readmissions [7], self-care [8], and quality of life [9], revealing that MI is an effective approach for improving self-care and outcomes in this patient population. Unfortunately, little is known regarding the specific mechanisms through which MI influences HF self-care.…”
Section: Introductionmentioning
confidence: 99%